Investigating Unexpected Shortening of Height of A Middle-Aged Woman: A Case Report - Muhtasim, Md Farhan; Persi, Abdullah Al; Khan, Mahjabin Nobi; Alim, Noor E Amrin; Hossain, Md Sazzad; Bhattacharjee, Pabitra Kumar (Bangladesh Journal of Nuclear Medicine, 2023)
Osteitis fibrosa cystica (OFC) is a late sequela of untreated hyperparathyroidism caused by the autonomous secretion of parathyroid hormone (PTH). It is characterized by bone pain, skeletal deformities, and pathological fractures. OFC is caused by hypersecretion of PTH, leading to demineralization of bone and pathological fractures. We report a case of unusual presentation of OFC in a middle aged woman who noticed gradual shortening of her height within a particular period of time. Apart from height reduction, the patient had weight loss and pain in different parts of the body for over a decade. Despite being treated with analgesics and steroids initially, there was no significant improvement in her condition. Treatment history included surgical reduction of right elbow fracture and empirical anti-tubercular drug twice as there was a suspicion of disseminated tuberculosis. The patient developed lytic changes, skeletal deformities, and osteoporosis, and was diagnosed with a solitary parathyroid adenoma on the right side. Bangladesh J. Nuclear Med. 26(1): 58-61, 2023